2000
DOI: 10.1002/(sici)1096-9888(200003)35:3<311::aid-jms918>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole ion trap studies of the structure and reactivity of transition metal ion pair complexes

Abstract: Ion pairs are common species observed in the electrospray mass spectra of transition metal coordination complexes. To understand the nature of these ion pairs, a systematic study of the gas‐phase chemistry of these species using ion–molecule reactions and collision‐induced dissociation (CID) was carried out. Ion pair complexes of the type MLnX+ (where M is Mn(II), Fe(II), Co(II), Ni(II), Cu(II) or Zn(II), L is 1,10‐phenanthroline, 2,2′‐bipyridine, ethylenediamine, diethylenetriamine or 1,4,8,11‐tetraazacyclote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 39 publications
3
60
0
Order By: Relevance
“…Reduction of Cu(II) to Cu(I) can occur upon dissociation of its complex with certain ligands such as bipyridyl° [23]°or°upon°reduction°of°Cu(II)°complexes°in°the reaction°with°solvents,°e.g.,°acetonitrile° [24,°25].°In°the ESI process, the reduction of Cu(II) to Cu(I) is much faster than the process in solution. Cu(I) is a closed-shell ion° [4],°which°may°explain°the°ease°of°this°reaction.…”
Section: Infusion Experiments (Cu(ii) and 22=-bipyridyl)supporting
confidence: 77%
“…Reduction of Cu(II) to Cu(I) can occur upon dissociation of its complex with certain ligands such as bipyridyl° [23]°or°upon°reduction°of°Cu(II)°complexes°in°the reaction°with°solvents,°e.g.,°acetonitrile° [24,°25].°In°the ESI process, the reduction of Cu(II) to Cu(I) is much faster than the process in solution. Cu(I) is a closed-shell ion° [4],°which°may°explain°the°ease°of°this°reaction.…”
Section: Infusion Experiments (Cu(ii) and 22=-bipyridyl)supporting
confidence: 77%
“…For species in which the complex contained the nitrate anion and coordinating alcohol molecules, multiple CID stages caused the elimination of two alcohol molecules and nitric acid to leave an ion pair composed Regardless of the coordinating anion, ESI produced gas-phase uranyl complexes that contained three solvent molecules, whether alcohol or H 2 O. Work by Vachet and Callahan [14] has suggested that the nitrate anion, within gas-phase transition metal complexes, is primarily a bidentate ligand. The acceptance of three additional ligands by the uranyl-nitrate ion pair is consistent with a hypothesis that ESI produces a gasphase complex with a pentagonal bipyramidal conformation reminiscent of the structure of uranyl complexes in the solution phase [5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…To gain a better understanding of the intrinsic interactions between different uranyl species and solvent, we have begun an investigation of uranyl-anion complexes in the gas phase using ion-trap mass spectrometry (IT-MS). Several recent reports have demonstrated that intrinsic metal and metal complex chemistry can be investigated by the (controlled) addition of reagent gas to an ion trap [12][13][14][15][16][17][18][19][20][21][22], or by way of the presence of H 2 O and other small molecule contaminants within the He bath gas used to collisionally cool ions and improve trapping efficiency [23][24][25]. The reactions of uranium ions in the gas phase have been the subject of several earlier investigations.…”
mentioning
confidence: 99%
“…Ion-molecule reactions in the gas-phase have been used extensively to gain information on the chemistry and reactivity of metals in coordination complexes, as well as the structures of these metal-ligand complexes [25][26][27][28][29][30][31][32][33][34]. In our studies, D 2 O and adventitious CD 3 OD were used as neutral reaction partners with several of the more abundant ions in Figure 1c to assess the degree of coordinative unsaturation of the uranyl in each of the selected species.…”
Section: Ion-molecule Reactions In the Gas-phase With D 2 O And Cd 3 mentioning
confidence: 99%